Improved outcome of 131I-mIBG treatment through combination with external beam radiotherapy in the SK-N-SH mouse model of neuroblastoma. Issue 3 (September 2017) - Corroyer-Dulmont, Aurélien; Falzone, Nadia; Kersemans, Veerle; Thompson, James; Allen, Danny P.; Able, Sarah; Kartsonaki, Christiana; Malcolm, Javian; Kinchesh, Paul; Hill, Mark A.; Vojnovic, Boris; Smart, Sean C.; et al.
Abstract: Purpose: To assess the efficacy of different schedules for combining external beam radiotherapy (EBRT) with molecular radiotherapy (MRT) using 131 I-mIBG in the management of neuroblastoma. Materials and methods: BALB/c nu/nu mice bearing SK-N-SH neuroblastoma xenografts were assigned to five treatment groups: 131 I-mIBG 24 h after EBRT, EBRT 6 days after 131 I-mIBG, EBRT alone, 131 I-mIBG alone and control (untreated). A total of 56 mice were assigned to 3 studies. Study 1: Vessel permeability was evaluated using dynamic contrast-enhanced (DCE)-MRI ( n = 3). Study 2: Tumour uptake of 131 I-mIBG in excised lesions was evaluated by γ-counting and autoradiography ( n = 28). Study 3: Tumour volume was assessed by longitudinal MR imaging and survival was analysed ( n = 25). Tumour dosimetry was performed using Monte Carlo simulations of absorbed fractions with the radiation transport code PENELOPE. Results: Given alone, both 131 I-mIBG and EBRT resulted in a seven-day delay in tumour regrowth. Following EBRT, vessel permeability was evaluated by DCE-MRI and showed an increase at 24 h post irradiation that correlated with an increase in 131 I-mIBG tumour uptake, absorbed dose and overall survival in the case of combined treatment. Similarly, EBRT administered seven days after MRT to coincide with tumour regrowth, significantly decreased the tumour volume and increased overall survival. Conclusions: This study demonstrates that combining EBRT and MRT has an enhanced therapeutic effect and emphasizes the importance of treatment scheduling according to pathophysiological criteria such as tumour vessel permeability and tumour growth kinetics.